Implementasi Pembiasaan Shalat Dhuha untuk Meningkatkan Kedisiplinan Peserta Didik Dalam Pembentukan Karakter Religius pada Kelas V di MI Mathla’ul Anwar Kota Bogor - Agustin, Nabila Rahma; Asmahasanah, Salati; Angelina, Putri Ria (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This thesis aims to find out, the Implementation of the Habit of Dhuha Prayer in Forming the Religious Character of Class V MI Mathla'ul Anwar Bogor Students. The Impact of the Implementation of Dhuha Prayer Habits in Forming the Religious Character of Class V MI Mathla'ul Anwar Bogor Students. This research uses a qualitative approach that is descriptive. Held from 1 January 2023 to 20 February 2023. The research location is at MI Marhla'ul Anwar Bogor. In the data collection procedure the authors use observation techniques, interview techniques and documentation techniques. Meanwhile, in data analysis, the researcher uses data collection, data reduction, data presentation and draws conclusions. The results of this study found that. Implementation of the habituation of the Dhuha Prayer was carried out before the learning process began, every day except Monday because there was a flag ceremony, where the Dhuha Prayer was held in the school field, from 07:00 to 07:30, while the background and purpose of the Dhuha Prayer as a superior program which is the hallmark of the school in providing positive refraction to students. The impact of the implementation of the habituation of the Dhuha Prayer in the formation of the religious character of students in class V MI Mathla'ul Anwar Bogor. Responsible, that is, when the time for prayer arrives, they no longer need to be ordered and ordered again in this matter, giving rise to the nature of responsibility in themselves in worship and learning in class. Key words: Habituation,Dhuha prayer Religious Character